Influence of preexisting preference for color on sampling and tracking behavior in bumble bees. (29th October 2018) - Maharaj, Gyanpriya; Horack, Patricia; Yoder, Marisa; Dunlap, Aimee S
Abstract : Animals must balance inherited bias with new information. Bumblebees frequently sample an innately preferred resource, but quickly leave when it varies in reward. This switch occurs even when the reward is potentially high. However, when innately preferred resources provide steady rewards the original preference remains. Bumblebees also take longer to sample other resources, are more likely to revisit that resource, and avoid variable resources when their preferred resources provide stable rewards. Abstract: Animals reduce uncertainty in their lifetime by using information to guide decision making. Information available can be inherited from the past or gathered from the present. Therefore, animals must balance inherited biases with new information that may be in conflict with those potential biases. In our study, we set up color pairings such that an arbitrarily chosen focal color, human-orange, would result in an inherent bias in comparison to 3 other colors tested resulting in equal, medium, and strong preference differences. We chose color pairings through a series of preferences tests across 8 colonies of bumble bees. We subsequently used these pairings with rewards that varied in quality (good or bad states) and consistency (steady and fluctuating) in order to investigate how inherited biases affect the foraging choices of bumble bees when new information is gathered. We found that the preexisting color biases within our bees were only maintained when the reward associated with those colors was steady, even if paired with mediocre sugar concentrations. When maintained, we observed that other aspects of bee choice also reflected this bias, including increased sampling for the preferred color and an increased likelihood of choosing that color in a subsequent choice. Thus, environmental change and reward differences interact with the level of preexisting bias to determine whether inherited information is more heavily weighted than newly gathered information, and even a strong preexisting bias can be quickly erased with experience under some conditions.